Upaya Meningkatkan Kepercayaan Diri Siswa Kelas IX H Melalui Bimbingan Klasikal Model Problem Based Learning Di SMP Negeri 1 Semarang - Risma Hesti Yuni Astuti; Suhendri, Suhendri; Indraswati, Veronica (Universitas Hamzanwadi, 2024)
Efforts to increase students' self-confidence can be done in several ways, one of which is using classical guidance. Classical guidance services are a method of guidance provided by guidance and counseling teachers to more than one student or what is usually called large group guidance. Classical guidance can be done through many techniques such as discussions using the Problem Based Learning model. Referring to the results of observations, discussions and pretest post-test results conducted by guidance and counseling teachers for class IX H students at SMPN 1 Semarang, it shows that students tend not to have high self-confidence. Students tend to be less active, afraid to express their opinions, hesitant, embarrassed if asked to speak in front of their friends, and anxious about their abilities when appointed by the counseling guidance teacher when in class. This research is a type of experimental research carried out in the form of a pre-experimental design. The research design applied was a one-group pretest-posttest design. This design has a pretest before action treatment and a posttest after action treatment. Based on the results of the pretest conducted by the guidance and counseling teacher, it was found that efforts were needed to increase students' self-confidence. The pretest results showed that out of 35 students, the percentage of self-confidence was 57.2%, they had very low self-confidence. Therefore, guidance and counseling teachers continue to strive to provide classical guidance in class IX H of SMPN 1 Semarang which is carried out through the first and second cycles. After carrying out the action, the next step is to carry out the post-test. The posttest results showed that the percentage of students' self-confidence had increased, of which 65.7% had high self-confidence